2019
DOI: 10.1155/2019/9290728
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Suppresses Self-Renewal Ability and Tumorigenicity of Osteosarcoma Stem Cells via Reactive Oxygen Species-Mediated Apoptosis and Autophagy

Abstract: Osteosarcoma is the most frequently diagnosed primary malignant bone sarcoma in children and adolescents. Recent studies have shown that cancer stem cells (CSCs), a cluster of tumor cells with the ability to self-renew, play an essential role in tumor recurrence and metastasis. Thus, it is necessary to develop therapeutic strategies specifically targeting CSCs. Metformin, the first-line drug for type 2 diabetes, exhibits antineoplastic activities in various kinds of tumors. New evidence has suggested that metf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…Moreover, the results suggested that metformin induced cytotoxicity by promoting cell cycle arrest in the G 2 /M phase and increasing apoptosis in CaSki and HeLa cells, and promoting G 0 /G 1 phase cell cycle arrest in c33a and Hela cells. Previous studies have illustrated the effects of metformin on the cell cycle in human osteosarcoma, demonstrating increased K7M2 and MG63 cell numbers in the G 0 /G 1 phase, and increased u20S and 143B cell numbers in the G 2 /M phase (49,56). Additionally, metformin has been reported to enhance anticancer effects by arresting human colon carcinoma cells in the G 0 /G 1 phase (SW480 cells) or the G 2 /M phase (HCT116 p53 −/− cells) (57,58).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the results suggested that metformin induced cytotoxicity by promoting cell cycle arrest in the G 2 /M phase and increasing apoptosis in CaSki and HeLa cells, and promoting G 0 /G 1 phase cell cycle arrest in c33a and Hela cells. Previous studies have illustrated the effects of metformin on the cell cycle in human osteosarcoma, demonstrating increased K7M2 and MG63 cell numbers in the G 0 /G 1 phase, and increased u20S and 143B cell numbers in the G 2 /M phase (49,56). Additionally, metformin has been reported to enhance anticancer effects by arresting human colon carcinoma cells in the G 0 /G 1 phase (SW480 cells) or the G 2 /M phase (HCT116 p53 −/− cells) (57,58).…”
Section: Discussionmentioning
confidence: 99%
“…Courtois et al [ 76 ] confirmed the anti-proliferative effect of metformin on gastric carcinoma cell lines by regulating the expression of genes implicated in cell-cycle regulation ( GADD45, p21, E2F1, and PCNA )[ 76 ]. Zhao et al [ 77 ] demonstrated that metformin inhibits the proliferation of osteosarcoma stem cells (OSCs) by inducing G0/G1 phase cell cycle arrest[ 77 ]. In a recent study, Barbieri et al [ 78 ] stated that metformin and other biguanides exert anti-proliferative effects in glioblastoma CSCs by interfering with the activity of the extracellular portion of the active transmembrane chloride ion channel.…”
Section: Effect Of Metformin On Cancer Stem Cellsmentioning
confidence: 99%
“…A recent study highlighted the strong dependence on energy-producing pathways of colorectal cancer CSCs, suggesting that modulation of AMPK activity is an effective therapeutic approach[ 81 ]. Zhao et al [ 77 ] showed that metformin induced caspase-mediated apoptosis in OSCs by inducing mitochondrial dysfunction. In addition, metformin influenced the capacity of OSCs to self-renew via enhanced autophagy, which was suppressed by 3-methyladenine, an inhibitor of autophagy[ 77 ].…”
Section: Effect Of Metformin On Cancer Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results further confirmed that Apelin overexpression rejuvenates AMSCs by activating autophagy. Accumulating evidence indicates that AMPK signaling plays a critical role in regulating autophagy ( Zhao et al, 2019 ; Khorraminejad-Shirazi et al, 2020 ). Next, we investigated whether Apelin mediates autophagy levels in AMSCs via this pathway.…”
Section: Resultsmentioning
confidence: 99%